Segmentation based on habit with respect to customer responses to sale promotions - Tran Nguyen, Bang Trang (2018)
Market segmentation is a core concept in modern marketing since consumers behaviours and preferences have become more and more diverse. The practice of segmentation assists companies in better discriminating and more efficiently allocating of resources to the most valuable groups of customers.